Evaluation of a peer-led asthma self-management program and benefits of the program for adolescent peer leaders - Rhee, Hyekyun; McQuillan, Brenda E; Belyea, Michael J (Respiratory care, 2012)
Asthma is the leading chronic condition in adolescents. Nonetheless, research efforts to address adolescent asthma morbidity by applying a developmentally appropriate self-management intervention have been limited. Recently a peer-led asthma self-management program has been developed and implemented for adolescents. The purpose of the study was to assess the acceptability of a peer-led asthma program for adolescents based on participant feedback and to examine the program's impact on asthma outcomes in peer leaders. Adolescents with persistent asthma (n = 91, 13-17 years) participated in a camp-based asthma program led by peer leaders (the intervention group) or healthcare professionals (the control group), and completed a set of program evaluation forms. Peer leaders (n = 14, 16-20 years) completed study questionnaires measuring asthma knowledge, self-efficacy, asthma control, and quality of life at baseline, immediately after camp, and 3, 6, and 9 months post-camp. The peer-led group reported more positive experience with the program than the adult-led group (P = .01, Cohen's d = 0.53), particularly in its usefulness in dealing with asthma. Peer leaders were rated by participants highly on knowledge (98%), attitudes (93-96%), personal skills (91%), and perceived similarities (80-86%). Significant improvements were found in peer leaders' knowledge (P < .001, η(2) = 0.87), self-efficacy (P < .001, η(2) = 0.74), asthma control (P = .01, η(2) = 0.66), and quality of life in emotional functioning (P = .002, η(2) = 0.82) and activity (P = .003, η(2) = 0.62). A peer-led asthma self-management program was successfully implemented and well received by adolescent learners. Asthma outcomes in peer leaders appear to have improved as a result of the program, although caution should be exercised in determining clinical meaningfulness, given the modest changes in mean scores. ClinicalTrials.gov registration NCT01161225.